A atividade criadora e suas manifestações: contribuições de Vigotski ao trabalho pedagógico - Strina Juliasz, Paula Cristiane (Anekumene, 2017)
A atividade criadora e suas manifestações: contribuições de Vigotski ao trabalho pedagógico